Closing down of publishing houses and catholic press in Poland in the second half of the forties of 20th century - Chmielewski, Witold (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The aim of this article is to present restrictions and gradual closing down of publishing houses and Catholic press in Poland after the Second World War. Accomplishing of this task resulted from communist ideological assumptions of the non-sovereign Polish state, which found itself under a strong influence of the Soviet Union. According to those assumptions, Polish society, especially its young generation, was to be secularized. Within a few post-war years, a vast majority of Catholic publishing houses was closed down and a number of books and magazine titles was dramatically reduced. The circulation of the still existing press and published books was small and clearly contrasted with fast growing propaganda and Marxist publications which were supported by the authority. The article is based on unknown archival sources. The subject needs further indepth research.
Keywords: catholic press; catholic magazines; catholic publishing houses